LOGOTHERAPY ON QUALITY OF LIFE IN CHRONIC KIDNEY DISEASE PATIENTS UNDERGOING HEMDOIALYSIS: A LITERATURE REVIEW - Putro, Dimas Utomo Hanggoro; Handayani, Buntar; Wahyuningsih, Sri Atun (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Background: Chronic kidney disease is a chronic disease that causes death rates to always increase. Chronic kidney disease patients require hemodialysis therapy. Hemodialysis therapy will have an impact on the quality of life of chronic kidney disease patients. Objective: This literature review aims to identify the effect of logotherapy on the quality of life of chronic kidney disease patients undergoing hemodialysis. Design: This research design is a literature review. Data Sources: Search for articles using three journal databases, namely Google Scholar, PubMed, and Science Direct. Review Methods: Used PRISMA flow diagram to find a total of 6 articles that met the inclusion criteria reviewed. Results: Keywords in English